Endobronchial ultrasound: a pictorial essay - Fantin, Alberto; Castaldo, Nadia; Tirone, Chiara; Sartori, Giulia; Crisafulli, Ernesto; Patrucco, Filippo; Vetrugno, Luigi; Patruno, Vincenzo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: endobronchial ultrasound has gained widespread popularity in the last decade, becoming the primary technique for minimally invasive evaluation of the mediastinum and staging of lung cancer. Several tertiary and quaternary care institutes use this method, performed by trained and accredited specialists. Its main indications are (I) diagnosis and staging of lung cancer, (II) mediastinal lymphadenopathy diagnosis (III) sampling peripheral pulmonary lesions.Conclusions: this manuscript aims to describe the operational potential of both convex endobronchial ultrasound probe and radial endobronchial ultrasound probe technology, focusing on lung cancer. This narrative review is complemented with by the description of peculiar clinical cases in which endobronchial ultrasound played a pivotal role in reaching the diagnosis.